Cynara scolymus L. extract and betaine supplementation in sows during lactation - Astúa-Ureña, Maikol (2023)
Introduction. The modern sow has the genetic capacity to produce a greater number of piglets per litter and a higher milk production, which means that the animal has higher nutrient requirements. Objective. To evaluate the performance of sows and their progeny to the supplementation of a commercial product based on artichoke dry extract (Cynara scolymus) and betaine hydrochloride during the lactation period. Materials and methods. The study was carried out during the first semester of 2020, in the province of Limón, Costa Rica. A total of 42 lactating sows were used and distributed in three treatments: control diet (T1), control diet + 0.25 kg t-1 of commercial product (T2), and control diet + 0.50 kg t-1 of commercial product (T3); the diets were isoproteic and isocaloric. Results. The inclusion of the additive showed a tendency to improve (p=0.09) the parameters evaluated in the sow. Body condition score loss was lower (p=0.03) with the T2, while supplementation with 0.50 kg t-1 presented intermediate results. There were no significant differences (p>0.05) between treatments for the parameters evaluated in the litters (weaning weight, weight gain, and number of weaned piglets by sow). Conclusion. The use of the additive showed a tendency to improve feed intake in the sow during the lactation period, reducing body weight loss and corporal condition during this period. The inclusion of the additive did not improve the performance in the piglets.